ONCE Stick and Onci dumpling: Local Food Supporting Economy Munding Tourism Village - Wijaya, M.Burhan Rubai (Seminar Nasional Pengabdian Kepada Masyarakat UNDIP 2020; Prosiding Seminar Nasional Kolaborasi Pengabdian Masyarakat UNDIP-UNNES 2019, 2020)
Munding Village is one of the villages in Bergas District, Semarang Regency. One of the main livelihoods of residents in the area is farmers. In this service, the writer focuses on one of the hamlets in Munding Village, namely Cemanggal Hamlet. In this area, in addition to the natural beauty that is very charming, it also has a main crop commodity, namely onclang leaves or we know that is very abundant leeks. However, the abundance of onclang is not matched by the good use of onclang leaves so that the utilization of onclang leaves is less than optimal and only sold directly in the form of leaves. For that the KKN PPM Munding Village has an idea on how to make onclang in the area into a product high-value local products that can increase the sale value and also improve the economy of villagers. The idea referred to here is training in making Oclang Cemangal Stick (ONCE) and also Onclang Cemanggal Dumplings (ONCI) for mothers in the Cemanggal area. The main purpose in devotion in this village is to improve the economy of citizens through various processed with basic ingredients onclang. Potential villages whose main commodity is onclang will advance the village economy with the right marketing process.